Cognitive performance of premature infants: Desempenho cognitivo de prematuros - Mello, Rosane Reis de; Reis, Ana Beatriz Rodrigues; Silva, Kátia Silveira da (São Paulo Medical Journal, 2017)
CONTEXT AND OBJECTIVE: Children born prematurely often have worse cognitive performance than those born at term regarding skills such as memory, attention and processing speed. Bronchopulmonary dysplasia may compromise cognitive development. The aims here were: a) To describe the cognitive performance of preterm infants with very low birth weight; b) To investigate its association with bronchopulmonary dysplasia adjusted for sociodemographic, neonatal and post-neonatal factors. DESIGN AND SETTING: Cross-sectional study developed in a public tertiary-care hospital. METHODS: To evaluate cognition among 112 children, we applied an intelligence scale (Wechsler scale). The average scores for children with and without bronchopulmonary dysplasia were compared across the five domains of the scale. Associations with bronchopulmonary dysplasia were investigated for domains that showed significant differences between the two groups. Associations between exposure and outcome were estimated via multivariate logistic regression. RESULTS: There were no differences in averages for the full-scale intelligence quotient, verbal intelligence quotient, performance intelligence quotient and general language composite domains. The processing speed quotient was the only domain that presented a significant difference between the two groups (P = 0.02). Among the children with bronchopulmonary dysplasia, low full-scale intelligence quotient was observed in 28.1%. In the multivariate analysis, bronchopulmonary dysplasia (odds ratio: 3.1; 95% confidence interval: 1.1-8.7) remained associated with the outcome of processing speed quotient. CONCLUSION: Bronchopulmonary dysplasia was an independent risk factor for alteration of the processing speed quotient.